Pendidikan Kesehatan Tentang Tahapan Tumbuh Kembang Untuk Deteksi Dini Stunting Balita - Khoirunnisa, Endang (LPPM STIKES Madani, 2023)
In the last ten years, there has been a spike in cases of malnutrition in several countries, thus making significantly reducing the incidence of stunting in children a global program. The main focus of attention on stunting is on the aspect of fulfilling nutrition, but educating parents about how to identify growth and development is an important first step in stunting prevention. This activity was carried out in Kepek, Timbulharjo Village, Sewon District, Bantul Regency, on Saturday, November 23, 2019, at 10.00–12.00 WIB. 35 mothers with toddlers participated in the activity. The method of implementing this service is carried out in two stages, each with a duration of 100 minutes, namely the measurement of height and weight and lectures and discussions about the identification of stunting in toddlers. The PKM team consists of lecturers, education staff, and students. The evaluation instrument was in the form of a closed-question questionnaire with a total of 10 items. The results of the first stage activity found 30 toddlers (85.71%) in the normal growth category and five toddlers (14.29%) in the below-standard category. increased knowledge about stunting identification by 62.20 points (from a mean score of 33 to 95.80). This activity is very helpful for mothers of toddlers to understand how to identify stunting and the risks experienced if the stages of child development are not in accordance with normal standards.